Technological detailed modeling and analysis of electrical energy use and CO2 emissions in Turkey within the framework of MARKAL based bottom-up national energy model - Yılmazer, Kadriye Büşra. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
In Turkey, as a fast developing country, demand for energy is growing each day. As energy’s strategic importance regarding sustainable economic growth, social and political stability gets greater; an energy modeling system that balances long and short term energy supply and demand, identifies possible bottlenecks, coordinates investments and financing, and foresees environmental impacts, a scenario based framework becomes inevitable. For the purpose of analyzing and better understanding the energy sector of Turkey and being able to predict how the energy sector will evolve in the future; a “bottom-up”, long-term energy supply and demand balance modeling system which is the “MARKAL” modeling system and the MARKAL-TURKEY model developed at Boğaziçi University are deployed in this study. Especially, the electricity generation sector of the MARKAL– Turkey model is analyzed and expanded with the aim of minimizing total costs and estimating total amount of greenhouse gas (GHG) emissions. Firstly, a reference scenario that reflects the status of Turkey’s energy system under current conditions and expected future trends is generated, and different “What-if” scenarios are developed by, (i) restricting CO2 emissions at a certain percentage, (ii) applying tax per tonne of CO2, (iii) changing fuel prices, (iv) forcing carbon capture and storage (CCS) technologies deployment and, (v) utilizing nuclear power. Together with the reference scenario, different realizations of these considerations and their combinations have led to the generation of a total of 30 scenarios (as the reference scenario and alternative scenarios). Finally, the results of each scenario are presented considering the electricity sector costs, the CO2 emissions and fuel consumptions. After the analyses of these results, concluding remarks are given.
Keywords: Carbon dioxide mitigation.; Electric utilities -- Government policy -- Turkey.